2015
DOI: 10.1200/jco.2015.61.9510
|View full text |Cite
|
Sign up to set email alerts
|

Epirubicin Plus Cyclophosphamide Followed by Docetaxel Versus Epirubicin Plus Docetaxel Followed by Capecitabine As Adjuvant Therapy for Node-Positive Early Breast Cancer: Results From the GEICAM/2003-10 Study

Abstract: Invasive disease-free survival, but not OS, was significantly superior for patients with node-positive early BC who received the adjuvant standard schedule EC-T than for those who received the experimental ET-X regimen. Toxicity profiles differed substantially across arms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 19 publications
0
44
0
Order By: Relevance
“…15 It is likely that these women would benefit from adjuvant treatment to improve outcomes, and several trials have evaluated escalation of adjuvant therapy. [16][17][18] The recently published CREATE-X trial 19 evaluated 910 patients with HER2-negative breast cancer who had residual invasive disease or LN metastases after NAC. Women were randomized to either adjuvant capecitabine or observation.…”
Section: Discussionmentioning
confidence: 99%
“…15 It is likely that these women would benefit from adjuvant treatment to improve outcomes, and several trials have evaluated escalation of adjuvant therapy. [16][17][18] The recently published CREATE-X trial 19 evaluated 910 patients with HER2-negative breast cancer who had residual invasive disease or LN metastases after NAC. Women were randomized to either adjuvant capecitabine or observation.…”
Section: Discussionmentioning
confidence: 99%
“…The adjuvant TACT 2 trial demonstrated that capecitabine has some advantages over standard CMF following anthracycline-based treatment [submitted, January 2017], because of lower toxicity and better quality of life with no apparent loss of efficacy. However, when capecitabine was added to docetaxel, doxorubicin and cyclophosphamide in the FINNXX trial 23 , there was no improvement in DFS and when capecitabine was substituted for cyclophosphamide in the GEICAM/2003-10 Study there was an increase in DFS events 24 . Nevertheless, there has been a recent renewal of interest, with the use of capecitabine after neoadjuvant chemotherapy in patients who had not achieved a pCR in the CREATE-X study 25 .…”
Section: Discussionmentioning
confidence: 99%
“…This adjuvant trial for patients with operable node-positive BC (T1-3/N1-3) compared 2 different 3-drug regimens, epirubicin plus cyclophosphamide followed by docetaxel vs. epirubicin plus docetaxel followed by capecitabine. 12 Patients who received ET-X did not receive cyclophosphamide in order to keep docetaxel and administer sequential capecitabine, although both arms received a regimen containing three drugs. Results of this study were surprising- the DFS results favored the control arm with a hazard ratio 1.30; 95% CI 1.03 to 1.64; log-rank p  = 0.03).…”
Section: Review and Analysis Of The Datamentioning
confidence: 99%